AB048. Solitary fibrous tumor of the trachea—the case of a rare neoplasm at a rare location - Cheva, Angeliki (Ann Transl Med, 2016)
BACKGROUND: To report an unusual neoplasm of a woman, 51, who presented with cough and dyspnoe. The CT scan of the thorax showed a mass, emerging from the membranous wall of the trachea. A surgical resection was undertaken. METHODS: We received a solid, yellowish-coloured, encapsulated mass of 6 cm in greatest diameter. RESULTS: The neoplasm offered areas of mild to moderate cellularity. The cells were spindle-shaped, with elongated or oval nuclei, and formed bundles, whirls or showed no particular pattern at all. The stroma was loose, with sparse signs of hyalinization or collagenization. There was no evidence of capsular invasion or necrosis. The mitotic activity was sparse (0–1/10 HPF). The neoplastic cells demonstrated the following immunophenotype: Vimentin+++, CD34+++, CD31−, CD117−, CK8/18−, EMA−, SMA−, Desmin−, S-100−, NSE−, GFAP−, Bcl 2−, CD99+/−. The Ki67 expression didn’t exceed <1%. These findings led us to the diagnosis of an extrapleural solitary fibrous tumor. CONCLUSIONS: Solitary fibrous tumor is a rare, benign, spindle-cell neoplasm, which was first described arising from the pleura. Its location may be thoracic or extrathoracic. In particular, it is estimated that the solitary fibrous tumor of the trachea accounts for only <0.05% of lung neoplasms. Neoplasms of this region, which should be considered in the differential diagnosis, include hemangiomas, neurogenic tumors, leiomyomas. The characteristic histologic findings consist of the presence of areas with variable cellularity, forming a “patternless pattern”, the short spindle-cells, the lack of necrosis, cytologic pleomorphism, or mitoses, as well as the positive expression of CD34, and the lack of expression for cytokeratins, S-100, SMA or EMA. Solitary fibrous tumors have low local recurrence or metastasis rates, following surgical treatment. Positive margins, greatest diameter larger than 10 cm, and the presence of areas with increased cellularity and mitotic activity are related to a worse prognosis. Nevertheless, given the questionable biologic behavior of this neoplasm, a close follow-up is always recommended.